Modelagem matemática na resolução de problemas do cotidiano - SILVA, Arlan Oliveira (2022)
The general objective of this work was to investigate in the teaching of Mathematics the contributions of Mathematical Modeling in solving everyday problems. Specifically, we sought to historically contextualize mathematical modeling; conceptualize and define modeling in mathematics education and, finally, verify the applicability of mathematical modeling in students' daily lives. It started with a bibliographic and qualitative research, whose collection of materials and information was based on articles, books, magazines and scientific publications on this subject. The analysis was descriptive, allowing the researcher to reduce the distance between theory and data, seeking to describe certain characteristics of the phenomenon studied. The results showed that Mathematical Modeling is a critical and creative way of acting in the reality of everyday life, allows greater student participation and is a current, open, flexible and dynamic methodology, being able to transform mathematics classes into spaces for construction. collective knowledge, done in a meaningful and enjoyable way. In this way, it is possible to affirm that there are already alternatives and possibilities of experiments that can be carried out inside the classroom, even with challenges, which are to overcome the theoretical study as a single basis, and to show the applicability of mathematical knowledge from the dialogue, allowing new learning methodologies in the classroom, relating mathematical knowledge to the students' daily lives.